THE USE OF THE KHWARAZMSHAH TITLE IN THE POWER SYSTEM OF THE KHIVA KHANATE (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Khwarazmshah” was a title attributed to the dynasties that ruled the Khwarazm oasis and was widely used as a political symbol over the centuries. This article analyzes how the Khiva khans employed this title to legitimize their rule on traditional and legal grounds. It also examines the ideological and political significance of the title and its role and status in the system of state governance.